Geography of ancient geometric earthworks and their builders in southwestern Amazonia - Kalliola, Risto; Pärssinen, Martti; Ranzi, Alceu; Seppä, Iiro; Barbosa, Antonia Damasceno (INST NACIONAL PESQUISAS AMAZONIA, 2025)
Geometric earthworks are evidence of ancient human activity in western Brazilian Amazonia. We used a review of existing and new data to map earthworks across 27,569 km2 of deforested areas in southwestern Amazonia using satellite imagery. We developed a conceptual basis for the classification of earthworks based on their structural characteristics using fuzzy sets. We recorded 1,279 structures with a distinctive core density zone. Most of the structures displayed geometric shapes, but they varied in construction accuracy. Geoglyphs accounted for 80% of all objects, with geographically variable shapes and enclosure areas. Other earthwork types included associated embankments, solitary embankments and mound sites. The abundance of earthworks provided evidence of strong pre-European human influence on the study area. A 10-km buffer around each earthwork included 75% of recent deforestation areas and 25.7% of standing forest, suggesting a significant potential for the presence of further earthworks in this ancient anthropogenic landscape and its possible far-reaching ecological legacy. The available radiocarbon data confirm a long-term anthropogenic impact in the study area, with ceremonial geoglyphs indicating activities over a thousand years old and other structures revealing more recent cultural transformations.